Systematic Literature Review: Research on Martial Arts Competition Using Vos Viewers in the 2018-2022 Google Scholar Database - Putu Citra Permana Dewi; Diah Primi Paramita; Qory Jumrotul Aqobah; Lesmana; Moch. Ali Akbar; Johaidah Mistar; Yasep Setiakarnawijaya (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2023)
Martial arts competition is a sport of self-defense skills that employs the ability to defend oneself, repel attacks and ultimately attack enemies, with or without weapons. This study uses a descriptive quantitative method with a bibliometrics approach. The research data used for scientific journals or articles spanning 2018-2022 is sourced from the Google Scholar database. A search for scientific articles was carried out using the Publish or Perish application with the keyword